1979
DOI: 10.3109/00016347909154068
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Bleeding in the Last Two Trimesters of Pregnancy a Clinical and Ultrasonic Study

Abstract: Ninety-seven cases of vaginal bleeding during the second and third trimesters of pregnancy are presented with special reference to the follow-up observations and perinatal parameters after the first bleeding and ultrasonic determination of placental site. The perinatal mortality rate was 11 per cent and the rate of premature deliveries 23 per cent. In the cases of recurrent bleeding episodes (N = 33), the corresponding frequencies were 22 and 35 per cent. Placenta previa of some degree was diagnosed by ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
(3 reference statements)
2
3
0
Order By: Relevance
“…The risk of PTB observed in our study (RR=3.9 [3.1-4.8] vs. control) is consistent with our previous findings (34.5% preterm birth) [5], with data previously reported by Ramaecker et al [8] (RR=1.56, 95% CI [1.14-2.14]) and with the meta-analysis of Ananth et al [11], which examined the outcomes of pregnancies complicated by bleeding (RR for PTB=2.2, 95% CI [2.1-2.4]). The recurrence of bleeding was associated with an increased rate of PTB in our series in agreement with the results reported by Yang and Jouppila (RR=1.7, 95% CI [1.2-2.3]) [6,12].…”
Section: Discussionsupporting
confidence: 92%
“…The risk of PTB observed in our study (RR=3.9 [3.1-4.8] vs. control) is consistent with our previous findings (34.5% preterm birth) [5], with data previously reported by Ramaecker et al [8] (RR=1.56, 95% CI [1.14-2.14]) and with the meta-analysis of Ananth et al [11], which examined the outcomes of pregnancies complicated by bleeding (RR for PTB=2.2, 95% CI [2.1-2.4]). The recurrence of bleeding was associated with an increased rate of PTB in our series in agreement with the results reported by Yang and Jouppila (RR=1.7, 95% CI [1.2-2.3]) [6,12].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, bleeding in the second trimester only, of a single episode, on a single day, and with less total blood loss was not associated with any category of preterm birth. 49 Recurrent bleeding predicted preterm birth more strongly than did single episodes, consistent with previous studies, as stated by Williams et al 50,51 However, a series of studies have demonstrated that APH is an independent factor for adverse neonatal outcomes in very preterm, as well as late preterm neonates. Among these groups APH has been independently associated with increased neonatal mortality and morbidity, particularly severe respiratory disorders, increased admission rate to NICU and increased hospital stay.…”
Section: Discussionsupporting
confidence: 83%
“…Uterine bleeding during the second and third trimesters is a relatively common complication of pregnancy, occurring in approximately 4% to 5% of antenatal patients and, from whatever cause, is associated with an increased incidence of premature births and perinatal deaths 1 . The causes of uterine bleeding in the second half of pregnancy include implantation of the placenta over or near the cervix (placenta praevia), premature separation of a normally implanted placenta (placental abruption), and the remainder in which the cause of the bleeding remains unknown (uterine bleeding of unknown aetiology).…”
Section: Introductionmentioning
confidence: 99%